Genetic divergence in forage sorghum (Sorghum bicolor L. Moench) (Journal of Applied and Natural Science, 2018)
Thirty genotypes of forage sorghum were studied for generating information on nature and magnitude of genetic variability and diversity for designing breeding programme. The experiment was conducted in randomized complete block design in three replications. The data were recorded on days to 50% flowering, plant height, leaf breadth, leaf length, leaf area, stem girth, leaves per plant, leaf stem ratio, total soluble solids, protein content and green fodder yield. Analysis of variance revealed a substantial amount of variability among the genotypes for all the characters under study, indicated a wide spectrum of variability among the genotypes. Highest estimates of the phenotypic coefficient of variation and genotypic coefficient of variation were observed for plant height, leaf breadth, leaves per plant, leaf stem ratio and green fodder yield. High heritability coupled with high genetic advance was observed for plant height, leaf area, stem girth, leaves per plant, leaf stem ratio and green fodder yield. Based on D2 – Statistics, 30 genotypes were grouped into six clusters. The highest inter-cluster distance was observed between cluster III and VI followed by IV and VI, indicating genotypes included in these clusters had wide genetic diversity. Genetic divergence and cluster mean indicates maximum heterosis and good recombinants may be achieved in crosses between genotypes of clusters III, IV and VI in varietal improvement programme. Thus, crossing between genetically diverse genotypes of cluster III with genotypes CSV 15, PC 1001, SPV 462, PC 3, SSV 84, PC 8 and cluster VI with genotype HJ 513 are expected to exhibit high heterosis and good recombinants with desired traits.